Structural basis for ryanodine receptor type 2 leak in heart failure and arrhythmogenic disorders - Marco C. Miotto; Steven Reiken; Anetta Wronska; Qi Yuan; Haikel Dridi; Yang Liu; Gunnar Weninger; Carl Tchagou; Andrew R. Marks (Nature Communications, 2024)
Abstract Heart failure, the leading cause of mortality and morbidity in the developed world, is characterized by cardiac ryanodine receptor 2 channels that are hyperphosphorylated, oxidized, and depleted of the stabilizing subunit calstabin-2. This results in a diastolic sarcoplasmic reticulum Ca2+ leak that impairs cardiac contractility and triggers arrhythmias. Genetic mutations in ryanodine receptor 2 can also cause Ca2+ leak, leading to arrhythmias and sudden cardiac death. Here, we solved the cryogenic electron microscopy structures of ryanodine receptor 2 variants linked either to heart failure or inherited sudden cardiac death. All are in the primed state, part way between closed and open. Binding of Rycal drugs to ryanodine receptor 2 channels reverts the primed state back towards the closed state, decreasing Ca2+ leak, improving cardiac function, and preventing arrhythmias. We propose a structural-physiological mechanism whereby the ryanodine receptor 2 channel primed state underlies the arrhythmias in heart failure and arrhythmogenic disorders.